Movimento da matemática moderna - de onde veio, qual foi o resultado? - Nielsen Junior, Kurt (2019)
In this work, we study the global Mathematics Modern reform Movement that reached its peak between the years of 1960 and 1990. It begins with a historical review of Math and enphatizes de work of french group Bourbaki. We intends show that Mathematics and in mathematics teaching are motivated by inherent factors of society. Next, we explored the influence of Bourbaki group influenced the greatest mathematics teaching reform movement. We observed the processes and the consequences, such as changes in the contents of school curriculum, in the methods and learning objectives and the necessity of an adequated training to mathematic teachers. At end, we analized arguments from critics and enthusiasts of this educational reform movemente and examined the impact of this movement on brazilian text books for basic and secundary education.